Belgium : 2018 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2018)
This 2018 Article IV Consultation highlights that the economic recovery in Belgium is gaining momentum, with real GDP growth expected to approach 2 percent in 2018 after an estimated 1.7 percent in 2017. It is driven by strong investment and solid consumption growth, and supported by favorable financial conditions as well as a strengthening recovery throughout Europe. Employment growth has picked up, thanks in part to past reform efforts. The fiscal position has improved, reflecting a mix of cyclical, structural, and one-off factors. The medium-term outlook, however, remains subdued in the absence of further structural reforms to raise potential growth, and subject to both external and domestic risks.